Numerical Study on the Dynamics of a Charged Bubble in the Acoustic Field - LV, Liang; LIU, Fei; LI, Yawei (Archives of Acoustics, 2024)
In this paper, the dynamics of an acoustic bubble with a constant charge in compressible liquid are investigated numerically, which is based on the Gilmore-NASG model to estimate the radial oscillations. The cavitation effects are enhanced due to the presence of the charge on the bubble surface. The obtained results from the present model are compared with that calculated by the previous model within a wide range of parameters (e.g., charge, acoustic pressure amplitude, ultrasound frequency, and liquid temperature). The similar influences of these parameters on bubble collapse intensity can be observed from both models. Since the present model fully considers the compressibility of gas and liquid, it can be applied to a wider parameter range and leads to the larger predicted values. The research in this paper can provide important insights about the effects of charge on bubble dynamics and the acoustic cavitation applications (e.g., sonochemistry, water treatment, and food industry)